Mouse Models of Rheumatoid Arthritis. (September 2015) - Caplazi, P.; Baca, M.; Barck, K.; Carano, R. A. D.; DeVoss, J.; Lee, W. P.; Bolon, B.; Diehl, L.
Rheumatoid arthritis (RA) is a chronic debilitating autoimmune disorder characterized by synovitis that leads to cartilage and bone erosion by invading fibrovascular tissue. Mouse models of RA recapitulate many features of the human disease. Despite the availability of medicines that are highly effective in many patient populations, autoimmune diseases (including RA) remain an area of active biomedical research, and consequently mouse models of RA are still extensively used for mechanistic studies and validation of therapeutic targets. This review aims to integrate morphologic features with model biology and cover the key characteristics of the most commonly used induced and spontaneous mouse models of RA. Induced models emphasized in this review include collagen-induced arthritis and antibody-induced arthritis. Collagen-induced arthritis is an example of an active immunization strategy, whereas antibody- induced arthritis models, such as collagen antibody–induced arthritis and K/BxN antibody transfer arthritis, represent examples of passive immunization strategies. The coverage of spontaneous models in this review is focused on the TNFΔ ARE mouse, in which arthritis results from overexpression of TNF-α, a master proinflammatory cytokine that drives disease in many patients.